The Roman Inquisition in the Italian Peninsula: Extension of Jurisdiction and 'Hispanization' of Procedures. A Case Study - Noto, Maria Anna (The Roman Inquisition in Malta and elsewhere, 2017)
With the Bull Cum primum apostolatus of 1566 Pope Pius V hints at adopting the secret denunciation to investigate and inflict severe penalties for the sins of sodomy, simony, bigamy, blasphemy and non-observance of worship and festivities. With the spectre of the 'cruel Spanish Inquisition' looming in the background, reactions take place in cities like Milan, Mantua, Modena, Naples and even Rome. A particularly violent reaction breakes out in Benevento, a papal city geographically included in the Kingdom of Naples, where popular riots blow up and cause the repressive intervention of papal authorities.